2012
DOI: 10.1002/bjs.8902
|View full text |Cite
|
Sign up to set email alerts
|

Role of serum carbohydrate antigen 19-9 and carcinoembryonic antigen in distinguishing between benign and invasive intraductal papillary mucinous neoplasm of the pancreas (Br J Surg 2011; 98: 104–110)

Abstract: Das 3,3′‐Pyrrolidinylspirooxindol‐System ist ein privilegiertes heterocyclisches Strukturmotiv, das die zentrale Einheit bei einer großen Familie von natürlichen Alkaloiden mit starken Bioaktivitätsprofilen und interessanten Struktureigenschaften bildet. Neue bedeutende Fortschritte bei der Synthese dieses kondensierten heterocyclischen Systems haben ein starkes Interesse an der Entwicklung verwandter Verbindungen als mögliche Wirkstoffe oder biologische Sonden hervorgerufen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…The serum tumor marker, CA199 (a tumorrelated carbohydrate protein), plays an important role in the diagnosis, treatment, and postoperative follow-up of pancreatic cancer. Increasing evidence indicates that serum CA199 levels play an important role in differentiating the benign and malignant properties of PCNs (25)(26)(27). Postlewait et al (28) analyzed the preoperative blood CA199 level of 349 cases of MCNs and found that the median CA199 level in the malignant group was 210 U/ml; in the nonmalignant group, the median CA199 level was only 15 U/ml (p = 0.001), suggesting that the elevated level of serum CA199 indicated malignant MCNs, which was consistent with the results of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The serum tumor marker, CA199 (a tumorrelated carbohydrate protein), plays an important role in the diagnosis, treatment, and postoperative follow-up of pancreatic cancer. Increasing evidence indicates that serum CA199 levels play an important role in differentiating the benign and malignant properties of PCNs (25)(26)(27). Postlewait et al (28) analyzed the preoperative blood CA199 level of 349 cases of MCNs and found that the median CA199 level in the malignant group was 210 U/ml; in the nonmalignant group, the median CA199 level was only 15 U/ml (p = 0.001), suggesting that the elevated level of serum CA199 indicated malignant MCNs, which was consistent with the results of the present study.…”
Section: Discussionmentioning
confidence: 99%